Comparative evaluation of surface roughness and impact strength of conventional polymethyl methacrylate and microcrystalline cellulose reinforced polymethyl methacrylate – An in vitro study - Thumma Sagar Reddy; Vinu Thomas George; Gauri Shahi; Sauptik Ray (The Journal of Indian Prosthodontic Society)
Aim: To evaluate and compare the surface roughness and impact strength of conventional polymethyl methacrylate (PMMA) with microcrystalline cellulose (MCC)-reinforced PMMA. Settings and Design: An in-vitro experimental study was conducted. Fifty PMMA specimens were fabricated and divided into five groups based on MCC concentration (2% or 5%) and particle size (20 μm or 50 μm). Materials and Methods: Specimens (80 mm × 10 mm × 4 mm) were categorized as follows: Group A (control; conventional PMMA), Groups B and D (2% MCC with 20 µm and 50 µm particles, respectively), and Groups C and E (5% MCC with 20 µm and 50 µm particles, respectively). Surface roughness was measured using a contact profilometer, and impact strength was tested with a ZwickRoell impact testing machine. Statistical Analysis Used: Statistical analysis was performed using IBM SPSS Version 28.0. One-way ANOVA followed by Tukey’s post hoc test was used to determine intergroup differences, with the significance level set at p<0.05. Results: Surface roughness was lower in Groups B (0.89±0.43), C (1.07±0.34), and E (0.77±0.27) compared to the control Group A (1.25±0.42), while Group D (1.84±0.25) showed higher values. Impact strength in Groups C (1.85±0.23), D (1.80±0.17), and E (1.81±0.26) was slightly lower than the control (1.88±0.31), though not statistically significant. However, Group B (1.56 ± 0.20) showed a significant reduction. Conclusion: The addition of 20 μm MCC reduced surface roughness at both 2% and 5% concentrations, whereas 50 μm MCC increased roughness at 2% but decreased at 5%. Impact strength remained comparable to the control in all groups except PMMA + 2% MCC (20 μm), which exhibited a significant decline. MCC reinforcement influences PMMA’s mechanical and surface properties, suggesting its potential for denture base modifications.